The effects of two directions of conflict and facilitation on frontline employees’ job outcomes - Karatepe, Osman; Kılıç, Hasan (Taylor and Francis, 2009)
This study investigated the effects of two directions of conflict and facilitation simultaneously on job performance, job satisfaction, and affective organisational commitment based on data obtained from frontline hotel employees in Northern Cyprus. As expected, family–work conflict dimished job performance, while family–work facilitation enhanced job performance. Contrary to our prediction, conflict between work and family domains intensified job performance. The results of the path analysis revealed that work–family facilitation increased job satisfaction, while family–work facilitation triggered affective organisational commitment. The findings pertaining to the relationships between job performance, job satisfaction, and affective organisational commitment were in the hypothesised directions. Also, the results of the confirmatory factor analysis demonstrated that the four-factor model that consisted of work–family conflict, family–work conflict, work–family facilitation, and family–work facilitation was superior compared with other models tested. Implications of the empirical findings and their future research directions are discussed in our study
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: MANAGEMENT, ROLE VARIABLES, SPOUSAL SUPPORT; ANTECEDENTS, CONSEQUENCES, MODEL; WORK-FAMILY CONFLICT, WOMEN, INTERFACE; BEHAVIORS, ORGANIZATIONAL COMMITMENT; Cyprus, Job satisfaction, Social aspects; Hotels and motels, Research, Employee performance; Performance evaluation, Discriminant analysis, Work life balance; Impact analysis, Studies, Commitments